Secondary Circulating Prostate Cell Positive Minimal Residual Disease Predict Biochemical Failure in Prostate Cancer Patients after Radical Prostatectomy - Murray, Nigel P.; Reyes, Eduardo; Orellana, Nelson; Fuentealba, Cynthia; Badinez, Leonardo; Olivares , Ruben; Porcell, Jose; Duenas, Ricardo (Perspective of Recent Advances in Medical Research Vol. 1, 2022)
The presence of circulating prostate cells (CPCs), one subtype of minimal residual disease, may be useful to predict patients at risk for biochemical failure (BF). The frequency of CPCs discovered following radical prostatectomy (RP), their relationship with clinicopathological characteristics, and their correlation with biochemical failure are all discussed. Following RP, serial blood samples were collected, mononuclear cells were isolated using differential gel centrifugation, and CPCs were detected using anti-PSA monoclonal antibodies in accordance with standard immunocytochemistry. The unadjusted biochemical failure free survival of patients with and without CPCs was compared using Kaplan Meier techniques. In the study, which included 114 men, secondary CPCs were found more frequently in patients with positive margins, extracapsular extension, and vascular and lymphatic infiltration. These findings also showed a shorter time to BF and an association between biochemical failure independent of these clinicopathological variables. Secondary CPCs are an independent risk factor for higher BF in men with a PSA <0.2 ng/mL following radical prostatectomy, but they do not distinguish between local and systemic disease recurrence.